If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -2a = 3a + -1 Reorder the terms: 3 + -2a = -1 + 3a Solving 3 + -2a = -1 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 3 + -2a + -3a = -1 + 3a + -3a Combine like terms: -2a + -3a = -5a 3 + -5a = -1 + 3a + -3a Combine like terms: 3a + -3a = 0 3 + -5a = -1 + 0 3 + -5a = -1 Add '-3' to each side of the equation. 3 + -3 + -5a = -1 + -3 Combine like terms: 3 + -3 = 0 0 + -5a = -1 + -3 -5a = -1 + -3 Combine like terms: -1 + -3 = -4 -5a = -4 Divide each side by '-5'. a = 0.8 Simplifying a = 0.8
| 3(r+8)-r=(5-r) | | r=4h+4z | | -100+30x+30x^2+30x^3+30x^4+30x^5=0 | | -15y=150 | | x+5=-17 | | 12(n+1)=15n-6 | | x^4-2x^3+6x^2=0 | | 9x-x=64 | | x^4+2x^3+6x^2=5 | | 6p+pq-8pq= | | x^4+2x^3+6x^2=0 | | p+13-3p=1-6p | | p-45=37 | | 20=4(x) | | -18-7x=2x+22 | | x^4+2x^3+6x^2=1 | | 5x+x=15 | | x^4+2x^3-6x^2=6 | | .9y-.7y=4.2 | | 18-4z+3-7z=8+5z-11-8z | | z=17+3(x+y) | | -2x+5+3x=5x+1 | | 8x-5=7x+2 | | 7-7x=97-42x+19 | | 4(8-3t)=5(2+t) | | n^2006+2n^2007=3 | | 2(b+5)=3(b-7) | | x^2*123+x^2= | | 7x-9=4x+24 | | -4(2p+4)-12=2(3p+7) | | 3(2m-1)=m+7 | | 4p^2-2p=0 |